An exploratory study on online misinformation appraisal behavior of undergraduate students from the University of the Philippines Diliman - Espina, Patricia Louise C.; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Information has always been a vital part of everyday life, starting from the process of gaining and sharing it through word of mouth to printed sources and at present through online platforms. Pairing the value of information with the continuous development of technology and popularity of the internet, information nowadays has become more susceptible to misinformation. In line with this exposure are various online information seeking behaviors of users.
There are two sides of the story when it comes to users' exposure to online misinformation, one side is from the creators while the other is the onlookers. This research presents the side of the creators through the known satire website The Adobo Chronicles while giving direct focus to online information users specifically the undergraduate students of the University of the Philippines Diliman.
An exploratory study was done through interviews from 100 undergraduate students who are presented 3 different articles published online that contained a mixture of factual information and misinformation. The respondents' appraisal of online misinformation was explained through these 4 factors : Informational subjective norm, Informational insufficiency, Negative affect and Perceived information gathering capacity ; which were all derived from the research's theoretical framework.
Collated responses projected that individual online seeking behavior, information subjective norm, information insufficiency, negative affect and perceived information gathering capacity affects a user's appraisal of online information credibility.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Fake news; Deception; Misinformation; Social media